Maturity Level of Client in the Implementation of Construction Safety Management System - Lubis, Dwiarta Agustina; Machfudiyanto , Rossy Armyn (Journal Research of Social Science, Economics, and Management, 2026)
The implementation of the Construction Safety Management System (SMKK) generally focuses on contractors because accidents often occur during construction work. However, construction safety is a shared responsibility among all parties involved in construction projects. This study aims to identify the safety maturity level of clients in the implementation of SMKK and to develop strategies to improve client safety maturity so that SMKK implementation can be enhanced. The measurement of client safety maturity used criteria based on the audit form attached to Permen PUPR No. 10 of 2021 concerning SMKK, which was validated by experts through two rounds of the Delphi method. Respondent samples were selected based on specific criteria using purposive sampling to obtain respondents who served as Budget User Representatives, Commitment-Making Officials, and Procurement Working Groups in the procurement of construction goods and services. Expert validation was used to assess the suitability of conditions and formulate strategies. The results of the study showed that the maturity level of clients was between reactive and compliant. Internal audits and management reviews by clients in the implementation of SMKK were generally conducted only when accidents occurred. To improve SMKK implementation, clients need to establish clear procedures as references for conducting audits and management reviews.